The Prevalence of Toxoplasma Gondii Infection in Duhok, Kurdistan Region, Iraq - Abdullah, A.M.; Abdullah, M.K.; Rasheed, R.M.; Azko, A.J.; Younis, Y.I.; Ahmad, H.O.; Majeed, S.A.; Абдулла, А.М.; Абдулла, М.Х.; Рашид, Р.М.; Азко, А.Д.; Юніс, Ю.І.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Toxoplasmosis is a parasitic infection, with widespread gestational and congenital transmission rates globally, consequently, it is regarded as a public health concern and an overlooked medical condition. Human infection occurs through various routes, including the ingestion of oocysts found in cat feces, consumption of raw or undercooked meat containing the parasite, and vertical transmission from an infected pregnant mother to her fetus. Objective. The aim of this study is to determine the prevalence of Toxoplasma gondii infection among individuals in various age groups and genders in Duhok City. Methods. In this research, 2251 individuals of various ages and genders visited the central laboratory in Duhok Сity, Kurdistan Region, Iraq, and peripheral blood samples were taken from individuals to identify specific anti-Toxoplasma gondii IgM and IgG antibodies using serological test (ELISA test). Results. Based on the findings of this study, it was observed that the prevalence of toxoplasmosis among females with infections detected in both IgM and IgG was 0.3 % and 20.6 %, respectively, and in males, the rate of infection with IgG was found to be 0.3 %, while no infections were detected with IgM. Also, among female individuals, the study recorded a 0.3 % infection rate for toxoplasmosis, which encompassed both IgM and IgG cases. Conclusions. Based on this study, it can be concluded that Toxoplasma infection is more common in females than in males, chronic toxoplasmosis appears to be more prevalent than acute infection with the highest rate of acute infections was found in the age group of 21–40 years.